Spatial co‐localisation of extreme weather events: a clear and present danger. (12th October 2020) - Dodd, Rosalind J.; Chadwick, David R.; Harris, Ian M.; Hines, Adrian; Hollis, Dan; Economou, Theodoros; Gwynn‐Jones, Dylan; Scullion, John; Robinson, David A.; Jones, David L.
Abstract: Extreme weather events have become a dominant feature of the narrative surrounding changes in global climate with large impacts on ecosystem stability, functioning and resilience; however, understanding of their risk of co‐occurrence at the regional scale is lacking. Based on the UK Met Office's long‐term temperature and rainfall records, we present the first evidence demonstrating significant increases in the magnitude, direction of change and spatial co‐localisation of extreme weather events since 1961. Combining this new understanding with land‐use data sets allowed us to assess the likely consequences on future agricultural production and conservation priority areas. All land‐uses are impacted by the increasing risk of at least one extreme event and conservation areas were identified as the hotspots of risk for the co‐occurrence of multiple event types. Our findings provide a basis to regionally guide land‐use optimisation, land management practices and regulatory actions preserving ecosystem services against multiple climate threats. Abstract : Extreme weather events have become a dominant feature of the narrative surrounding changes in global climate with large‐scale implications for ecosystem function. Based on the UK Met Office's long‐term high‐resolution temperature and rainfall records, we present the first evidence demonstrating significant increases in the magnitude, direction of change and spatial co‐localisation of extreme weather events since 1961. Combining this new understanding with land‐use data sets allowed us to assess the likely consequences of these events on future agricultural production and conservation priority areas.